2009
DOI: 10.1002/met.119
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and enhancing the public's behavioural response to flood warning information

Abstract: Drawing on evidence from the United Kingdom and elsewhere in Europe, this paper explores how people have responded to flood warning information and how these responses impact upon the effectiveness of a flood warning through saving lives and injuries, and reducing economic damages. Methods of flood warning that the public rely upon are discussed alongside empirical evidence of how flood victims prepare for, and respond to, flood warnings in rapid to medium-onset floods. The paper investigates why some members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
181
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(183 citation statements)
references
References 28 publications
2
181
0
Order By: Relevance
“…It should also address emotions and raise the addressees' interest in the topic. As Parker et al (2009) claims, effective flood communication stimulates the addressees to wonder about their environment and to question their safety in it. Our data confirmed that the campaign motivated almost half of the respondents to talk about the topic in private circles.…”
Section: Raising Awareness Knowledge and Information Behaviourmentioning
confidence: 99%
“…It should also address emotions and raise the addressees' interest in the topic. As Parker et al (2009) claims, effective flood communication stimulates the addressees to wonder about their environment and to question their safety in it. Our data confirmed that the campaign motivated almost half of the respondents to talk about the topic in private circles.…”
Section: Raising Awareness Knowledge and Information Behaviourmentioning
confidence: 99%
“…Older people in the United Kingdom also reacted more positively to a knock on their door by flood wardens than to some flood warning technologies (e.g. dial-and listen flood warning services), which they found less user-friendly (Parker et al 2009). …”
Section: Knowledge and Attitudinal/motivational Capacitiesmentioning
confidence: 99%
“…It also suggests that property-level adaptation measures are insufficiently promoted, citing Harries" (2008a) finding that fewer than 6% of at-risk householders who have never been flooded have implemented even the simplest forms of such measures. Similarly, although awarenessraising and flood warnings have received significant investment, warning systems are seen as inadequate by flood victims (Parker et al, 2009) and two-fifths of residents of atrisk areas remain unaware that they are at risk (Harries 2008a). …”
Section: The Changing Policy Contextmentioning
confidence: 99%